Perubahan Struktur Ekonomi dan Dampaknya Terhadap Kemiskinan di Provinsi Jambi - M. Andi Alfarabi; M. Syurya Hidayat; Selamet Rahmadi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
The purpose of this research is to know changes the structure economy in the range of time  in  1996 – 2009  and  the  all  factors  that  affect  changes  the  structure  economy  was  also  know  the impact of career safety and a reduction poverty in Provinces Jambi. Of Result research is so well known changes structure economic that was started  with  growth  economic a then had an impact on  in  changes  pattern  consumption  society  relative  low,  but  there is a shift in 1996-1997.  advanced  known  factors-  factors  that  affect  changes  the structure  in  Province  Jambi  which  is divided  according to his  sector  (primary, industry, tools & services). Then  impact  changes  the  structure  economic  in  Province  Jambi  to : (a)  Career Summary : changes structure economic that  happened  in  Provinces  Jambi  (four  sectors economy)  did  not  have an effect  on  significant  the  enforced  career  safety  in  Province Jambi; (b) Poverty: only share sector industry and share the sector  tools  that  have  influence  significant  to decrease the number poverty in Province Jambi.Keywords: Poverty, Sector Economy, Career Safety